Electrochemical Impedance Spectroscopy Evaluation of Non-Metallic Pipe (NMP) Degradation in CO2 Environment - Ab. Aziz, Muhammad Yusri Hafiz (IRC, 2020)
The utilization of Non-Metallic Pipe (NMP) as part of recent corrosion control and management practise has create a critical requirement in term of corrosion monitoring of the NMP as it exposed to field operating condition. Currently, there is no established method to monitor the corrosion activities in NMP. Hence, this study was initiated to evaluate the capability of an advance monitoring technology namely Electrochemical Impedance Spectroscopy (EIS) in detecting the chemical degradation of NMP when exposed to CO2 corrosion environment. The chemical degradation process on a selected types of polymer, High-density Polyethylene (HDPE) and the electrochemical impedance analysis were conducted comprehensively. The chemical degradation process was held in an autoclave machine with fixed temperature and pressure setup. The chemical deterioration of polymer have proven by assessing under EIS which based on EIS reading such as Nyquist and Bode Plot that identify the salient characteristic of corrosion damage in polymer. As a conclusion, this project can give a practical quantitative monitoring method in future NMP application. However, the research was recommended to continue the studies by using stronger and thinner polymer in order to avoid the sample from melting and for better result.